Assessment of relief valves (rv) performance in petronas carigali, sarawak operations, Miri - Labon, Patrick (2000)
The objective of conducting this study is to asses the performance of various types of relief valves (RVs) installed on the platforms of PETRONAS CARIGALI SDN BHD, Miri, Sarawak in the offshore facilities. There is a strong concern on the impact of the certification process of relief valves. It is not only risky but incurs downtime and deferment of crude oil and gas production. At the end of this study, a various model or types of RVs performance are compared. Collection of data is taken from a secondary source from the contractor’s workshop that is contracted to do the relief valve certification work. The data available is a sample of some relief valves that have undergone the certification process for the last three years, 1998 up to 2000. The major variables used in the data consist of RV Model, RV Designed Set Pressure, Pop Test Pressure, and calculation of Error percentage. A total of 543 RVs pop test data were collected. The observation is that 40% of the overall RV sample collected shows good performance while 20% were found leaking. The other 40% popped either beyond or before the healthy range of set pressure. Overall this means, 60% of the RVs at the offshore platforms are not performing according to their original design. These RVs are further categorized by their model. The majority of the models used are AND Greenwood and Cosby models which have at least 20% of the units leaking – 20% and 28% respectively.